Development and in vitro Evaluation of Sustained Release Matrix Tablets of Indapamide from Methocel® K15 MCR and K100 LVCR (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Indapamide, a low-dose thiazide-type diuretic, is used for the treatment of essential hypertension. In this study, we developed an indapamide sustained release formulation using Methocel K15 MCR (a modified    hydroxypropyl methylcellulose), Methocel K100 LVCR (a modified hydroxypropyl methylcellulose), magnesium stearate, talc and starch 1500 by direct compression. The powders for tableting were evaluated for angle of repose, loose bulk density, tapped bulk density, compressibility index, total porosity etc. The tablets were subjected to thickness, weight variation test, hardness, friability and in vitro release studies. The in vitro dissolution study was carried out in the gastric medium (pH 1.3) for first two hours and then in the intestinal medium (pH 6.8) for 22 hours using United States Pharmacopoeia (USP) 22 paddle-type dissolution apparatus. The granules showed satisfactory flow properties, compressibility index etc. All the tablets complied with pharmacopoeial specifications. The results of    dissolution studies indicated that the formulation F-5 and F-7 (up to 75.36 % drug release in 12 hours) could extend the drug release up to 12 hours. The drug release patterns were simulated in different kinetic orders such as Zero Order release kinetics, First Order release kinetics, Higuchi release kinetics, Korsmeyer-Peppas release kinetics and Hixson-Crowell release kinetics to assess the release mechanism. From the study we observed that Higuchi release    kinetics was the predominant release mechanism than Zero Order and First Order kinetics. The drug release mechanism from the matrix tablets was found to be non Fickian mechanism.   DOI: http://dx.doi.org/10.3329/dujps.v10i2.11785   Dhaka Univ. J. Pharm. Sci. 10(2): 87-92, 2011 (December)